Frontispiece: NMR Spectroscopic Assignment of Backbone and Side‐Chain Protons in Fully Protonated Proteins: Microcrystals, Sedimented Assemblies, and Amyloid Fibrils. Issue 50 (5th December 2016) - Stanek, Jan; Andreas, Loren B.; Jaudzems, Kristaps; Cala, Diane; Lalli, Daniela; Bertarello, Andrea; Schubeis, Tobias; Akopjana, Inara; Kotelovica, Svetlana; Tars, Kaspars; Pica, Andrea; Leone, Serena; et al.
Abstract : Protein Structures G. Pintacuda et al. show in their Communication onpage 15504 ff. that with 111 kHz magic‐angle spinning probes, high‐resolution 1 H‐detected solid‐state NMR spectra of proteins can be acquired without deuteration.